4D pine scale: biomimetic 4D printed autonomous scale and flap structures capable of multi-phase movement. (3rd February 2020) - Correa, David; Poppinga, Simon; Mylo, Max D.; Westermeier, Anna S.; Bruchmann, Bernd; Menges, Achim; Speck, Thomas
Abstract : We developed biomimetic hygro-responsive composite polymer scales inspired by the reversible shape-changes of Bhutan pine ( Pinus wallichiana ) cone seed scales. The synthetic kinematic response is made possible through novel four-dimensional (4D) printing techniques with anisotropic material use, namely copolymers with embedded cellulose fibrils and ABS polymer. Multi-phase motion like the subsequent transversal and longitudinal bending deformation during desiccation of a natural pinecone scale can be structurally programmed into such printed hygromorphs. Both the natural concept generator (Bhutan pinecone scale) and the biomimetic technical structure (4D printed scale) were comparatively investigated as to their displacement and strain over time via three-dimensional digital image correlation methods. Our bioinspired prototypes can be the basis for tailored autonomous and self-sufficient flap and scale structures performing complex consecutive motions for technical applications, e.g. in architecture and soft robotics. This article is part of the theme issue 'Bioinspired materials and surfaces for green science and technology (part 3)'.